Clinical Results of Posterior Decompression in Lumbar Spinal Stenosis with Modic Change Type1 - Murotani, Kazuhiro; Tamaki, Yasuyuki (Journal of Spine Research, 2022)
Introduction: Clinical results of posterior decompression surgery for lumbar spinal canal stenosis with Modic change Type1 were examined.Methods: Subjects included 122 cases of lumbar spinal canal stenosis that underwent spinous process-splitting laminectomy. Seventy-eight cases were men and 44 were women, with an average age of 72 years and a follow-up period of approximately 303 days. Subjects were compared by dividing them into two groups, group M of 29 and group NM of 93 cases, with and without Modic change Type1.Results: Average improvement ratio of JOA score and VAS variation of lower back and lower leg pain as well as lower leg numbness observed in group M and NM were 55.6% and 58.2%, 14.0 mm and 22.5 mm, 18.0 mm and 35.8 mm, and 22.3 mm and 30.9 mm, respectively. Scores of group M and NM obtained in JOABPEQ regarding disorders relating to pain, functional disorder caused due to back pain, locomotor function disorder, social life disorder, and psychological disorder were 26.1 and 22.4 points, 9.4 and 11.8 points, 21.1 and 22.6 points, 16.6 and 17.7 points, and 9.0 and 7.8 points, respectively.Conclusions: Even with Modic change Type1, low back pain, lower limb pain and lower limb numbness may still persist; however, other clinical results were not influenced in posterior decompression for lumbar spinal canal stenosis.